Impacto del cambio climático en la postcosecha de cítricos. - Bajaña Peralta, Yulexi Margarita (2025)
In Ecuador, specifically the Ecuadorian coast, there is great potential to produce citrus fruits to satisfy domestic consumption. Climate change has beneficial effects on citrus fruits, such as greater tolerance to high temperatures through increased transpiration, which can also increase the area of photosynthetic surface. The main objective of the research was to determine the impact of climate change on the post-harvest of citrus fruits. The document was prepared by compiling updated information from scientific articles and online libraries, focusing on a non-experimental design. The conclusions presented indicate that citrus fruits are especially marketed post-harvest, since their quality, durability, and marketing depend on climatic conditions. It is preferable to harvest in dry weather to maintain fruit quality, since humidity can promote the growth of molds and other harmful pathogens. Citrus postharvest causes physiological disorders such as fruit puffing, chilling lesions, skin degradation, and gray spots, all of which are favored by low temperatures and low humidity. Low temperatures can cause various types of damage in citrus postharvest due to the impact of climate change. These include alterations to the fruit cuticle, such as lesions and cracks in the epicuticular waxes. The physiological changes that citrus fruits can experience during storage affect their quality and durability due to their susceptibility to low temperatures, posing a major challenge to the preservation and marketing of these products.